2012
DOI: 10.1111/j.1365-2966.2012.20952.x
|View full text |Cite
|
Sign up to set email alerts
|

Towards a unified model of stellar rotation - II. Model-dependent characteristics of stellar populations

Abstract: Rotation has a number of important effects on the evolution of stars. Apart from structural changes because of the centrifugal force, turbulent mixing and meridional circulation caused by rotation can dramatically affect a star’s chemical evolution. This leads to changes in the surface temperature and luminosity as well as modifying its lifetime. Observationally, rotation decreases the surface gravity, causes enhanced mass loss and leads to surface abundance anomalies of various chemical isotopes. The replicat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…binary merger, mass transfer or common evelope evolution (Ferrario et al 2009;Langer 2012). Finally, the fields could be generated by a dynamo process inside the the main sequence star (Spruit 2002;Potter et al 2012b). We emphasize that these three alternatives predict different time-dependances of the stellar rotation and magnetic field incidence, which might be testable if the age distribution of our sample stars can be established.…”
Section: Magnetic Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…binary merger, mass transfer or common evelope evolution (Ferrario et al 2009;Langer 2012). Finally, the fields could be generated by a dynamo process inside the the main sequence star (Spruit 2002;Potter et al 2012b). We emphasize that these three alternatives predict different time-dependances of the stellar rotation and magnetic field incidence, which might be testable if the age distribution of our sample stars can be established.…”
Section: Magnetic Fieldsmentioning
confidence: 99%
“…It may affect both how the star evolves during hydrogen core burning (see, for example, Brott et al 2011;Potter et al 2012b) and the nature of any supernova explosion (see, for example Woosley & Heger 2006;Yoon et al 2006). It can also provide insights into other phenomena such as star formation Tables 3 and 4 are only available at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsarc.u-strasbg.fr/viz-bin/qcat?J/A+A/550/A109 Hubble Fellow.…”
Section: Introductionmentioning
confidence: 99%
“…For example, synthetic stellar populations computed by Brott et al (2011) andPotter et al (2012) cannot reproduce several groups of stars observed by Hunter et al (2009), notably nitrogen-rich slow rotators. Note that the existence of these stars might be explained by rotational mixing if some braking is active at the surface, for instance due to a surface magnetic field (Meynet et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to the progress in the computational efficiency of such codes, it is now possible to compute entire synthetic stellar populations from a given distribution of initial conditions that include chemical composition and angular momentum. As shown by Brott et al (2011) and Potter et al (2012), these synthetic populations can be compared to observed ones, such as those obtained by large surveys. In particular, the authors recover the main group of stars observed by Hunter et al (2009).…”
Section: Introductionmentioning
confidence: 99%